Short-term, manualized schema-focused group therapy for patients with CBT-resistant disorders within primary care: a pilot study with a naturalistic pre-treatment and post-treatment design - Kiers, Ingeborg L.; de Haan, Hein A. (Frontiers in Psychology, 2024)
The aim of this study was to explore the feasibility and preliminary effectiveness of a short-term, manualized schema therapy group for 77 patients with CBT-resistant mood and/or anxiety and/or personality disorders (PDs) in primary care. The primary focus was on the effects of this treatment on Early Maladaptive Schemas (EMS), schema modes, and psychological well-being.These aspects were assessed pre-and post-treatment treatment using the Young Schema Questionnaire (YSQ), the Schema Mode Inventory version 1.1 (SMI), and the Symptom Questionnaire-48 (SQ-48). The treatment consisted of 16 sessions, incorporating cognitive, behavioral, and experiential techniques. EMS significantly decreased from pre-treatment to post-treatment, as along with maladaptive schema modes. Adaptive modes increased, as did psychological wellbeing. There were no significant differences between the DSM-5 classifications regarding changes in the aforementioned measures, except for the maladaptive modes, where the value of the corrected within-subject effect indicated a significant interaction. Post hoc comparisons were therefore conducted (see Table 3) which showed that patients with a mood disorder experienced more positive changes in maladaptive modes compared to patients with anxiety disorders and PDs (p<.001). There was no significant difference between those with PDs and those with Anxiety Disorders.Our findings provide preliminary evidence that short-term, manualized schema therapy might be an effective treatment for patients with CBT-resistant mood and/or anxiety and/or PDs in primary care.